Effects of nutrition education intervention model on complementary feeding practices among parents in a defined area in Kalutara District in Sri Lanka - Gunawardhana, S.R.H.P (My University, 1999)
The study comprised three phases namely situation analysis, development and implementation of the intervention model and evaluation. Analysis of data revealed, that knowledge on aspects of weaning such as age of introduction of different food items, frequency of feeding, amount of feeds, and feeding during an illness were inadequate. Knowledge of public health midwives regarding complementary feeding was also deficient. Only few health education materials were available. There was a significant improvement in knowledge of mothers as well as fathers, on age of introduction of different food items, frequency of foods, amount of feeds and feeding during an illness in the intervention group, when compared with the control group. Mean hemoglobin level also showed significant improvement in infants in intervention area when compared with the control group. However, weight and length measurement showed no significant difference between the intervention group and the control group. This study showed that the nutrition education itself could not achieve positive effects on growth of an infant. Nutritional education together with improvement in living conditions is likely to result in a significant improvement in nutritional status